The tension between cross-border cooperation in the European Area of Freedom, Security and Justice and the fundamental rights of mentally ill offenders in detention. (July 2016) - Meysman, Michaël
Abstract: In two recent judgements, the European Court of Human Rights (ECtHR) has given an alarming signal regarding the placement, care and treatment of mentally disordered offenders in Belgium. This article analyses these judgements and the Court's assessment that Belgium faces a structural problem regarding the detention of people with a mental illness in prison. By exploring other recent ECtHR decisions across the EU and combining this with an analysis of international norms and standards, it contends that there is something amiss regarding the post-trial approach towards mentally disordered offenders in an EU-wide context. The potential hazards of this situation, from both an individual and an EU perspective are then presented by analysing the EU Framework Decision on the transfer of prisoners (which aims to facilitate offender rehabilitation) and the EU Court of Justice's interpretation of the relationship between instruments like the Framework Decision that are based on mutual recognition and fundamental rights. Lastly, the EU's initiative for enhancing procedural rights in criminal proceedings through the Roadmap trajectory, and the subsequent Commission Recommendation of 27 November 2013, are scrutinized. Based on this research, the article pinpoints the flaws and vacuums that currently exist for mentally disordered offenders, and the negative outcome this may have on the legitimacy and effectiveness of the European Area of Freedom, Security and Justice.